3D-printed Mg-incorporated PCL-based scaffolds improves rotator cuff tendon-bone healing through regulating macrophage polarization - Wang, Tao; Yu, Ziqing; Lin, Shaozhang; Chen, Zhaohuan; Jin, Han; Liang, Lin; Zhang, Zhi-Yong (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: Rotator cuff tear (RCT) is a common shoulder injury impacting mobility and quality of life, while traditional surgeries often result in poor healing. Tissue engineering offers a promising solution, with poly (ε-caprolactone) (PCL) being favored due to its slow degradation, biocompatibility, and non-toxicity. However, PCL lacks sufficient compression resistance. Incorporating Mg, which promotes bone growth and has antibacterial effects, could enhance RCT repair. Methods: The Mg-incorporated PCL-based scaffolds were fabricated using a 3D printing technique. The scaffolds were incorporated with different percentages of Mg (0%, 5%, 10%, 15%, and 20%). The osteogenic activities and anti-inflammatory properties of the scaffolds were evaluated in vitro using human osteoblasts and macrophages. The tissue ingrowth and biocompatibility of the scaffolds were assessed in vivo using a rat model of RCT repair. The ability of the scaffolds to enhance macrophage polarization towards the M2 subtype and inhibit inflammation signaling activation was also investigated. Results: It was found that when incorporated with 10% Mg, PCL-based scaffolds exhibited the optimal bone repairing ability in vitro and in vivo. The in vitro experiments indicated that the successfully constructed 10 Mg/PCL scaffolds enhance osteogenic activities and anti-inflammatory properties. Besides, the in vivo studies demonstrated that 10 Mg/PCL scaffolds promoted tissue ingrowth and enhanced biocompatibility compared to the control PCL scaffolds. Furthermore, the 10 Mg/PCL scaffolds enhanced the macrophages’ ability to polarize towards the M2 subtype and inhibited inflammation signaling activation. Discussion: These findings suggest that 3D-printed Mg-incorporated PCL scaffolds have the potential to improve RCT by enhancing osteogenesis, reducing inflammation, and promoting macrophage polarization. The incorporation of 10% Mg into PCL-based scaffolds provided the optimal combination of properties for RCT repair augmentation. This study highlights the potential of tissue engineering approaches in improving the outcomes of RCT repair and provides a foundation for future clinical applications.